Analytical Approach to Estimate the Rheological Properties of Asphalt Binders. Issue 1 (January 2014) - Kabir, Pooyan; Sakhaeifar, Maryam S.; Newcomb, David
The importance of rheological properties of bituminous materials has grown in the United States since the early 1990s, in line with the SHRP. These rheological properties are now commonly used in materials specifications and as input into the Mechanistic–Empirical Pavement Design Guide. Thus an approach that used predictive models to estimate accurately the rheological properties of bituminous materials would be useful for pavement design. In the study reported here, a modeling approach was proposed with a basis in fundamental viscoelastic principles. To establish the models, a large data set, which was obtained from multiple efforts from numerous locations across the United States, was used. The database consisted of measured modulus values from mixtures with modified and unmodified binders and mixtures that had various amounts of reclaimed asphalt pavement (RAP). As a result, two predictive models were developed to estimate the binder shear modulus and phase angle, given the desired physical and mechanical properties of asphalt mixtures. These models could be used for the wide range of temperatures (from 2108 to 54.48C) recommended in the AASHTO TP62-03 test protocol. The predictive capabilities of the newly developed models were evaluated with the use of different data sets with various types of mixtures. The findings of this study should lead to enhanced knowledge of the rheological properties of binders in RAP mixtures at intermediate and high temperatures without the need to extract the binders from the mixtures.